Analysis of Labor Law Regarding Protection Labor Wages Under the Law Number 13 Year 2003 on Manpower - Lidia Febrianti; Syafrinaldi; Efendi Ibnu Susilo; Thamrin S (International Conference On Law And Social Sciences, 2024)
One of the protections in labor issues is a decent wage for workers. Because wages are the goal of workers in doing work. Every activity carried out by workers contains aspects of social relations, legal relations, and inter-organizational relations that give rise to rights and obligations, and are carried out based on the values contained in Pancasila. In labor relations, the rights and obligations of various parties are regulated through Law No. 13 Year. 2003 regarding employment, one of the core regulations is regarding wages. Wages are the right of workers to be compensated for work performance determined by convention and payment is made in accordance with the agreement. Wages are also a constitutional right for citizens which is also explained through the 1945 Constitution Article 27 paragraph 2, which states that every citizen has the right to work and a decent livelihood. The constitutional right was explained in the regulation of Law No. 13 of 2003 related to employment (Law No. 13 of 2003) in Article 1 paragraph 30 reveals that wages are the rights of workers who are obtained and expressed in the form of money which is a reward. Then what is meant by using wages to fulfill the needs of life with feasibility, it will cause the welfare of workers. This is also stated in Article 1 paragraph (31) of Law No. 13 of 2003, which states that worker welfare is a fulfillment of physical and spiritual needs and needs. Thus, wages are a component of work interaction based on an agreement, which has a work component of wages and instructions. This research is a normative legal research using literature review to obtain secondary data, in the form of laws and regulations and various legal documents, as well as other relevant references.